Public Relations & Media Relations (Kritik Budaya Amplop Pada Media Relations Institusi Pendidikan Di Yogyakarta) - Adhianty Nurjanah; Wulan Widyasari; Frizky Yulianti N (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2015)
AbstractThis research is aims to determine how the media relations activities that have been done 10 Public Relations Higher Education, including the possibility of granting cultural envelope in media relations activities during this do. The object of this study is ten (10) Universities in Yogyakarta that consists of three (3) State University (PTN) and seven (7) Colleges (PTS). Variations and types of media relations activities have been conducted by 10 universities. The reason is because the electoral college to ten (10) college is a big college in the city of Yogyakarta who own Public Relations and media relations activities that have a systematic and well-planned. In the course of media relations, Public Relations universities do culture accepting envelopes to reporters on the grounds reimburse the costs of transport and not as a